Penerapan Model Pembelajaran Kuantum pada Matakuliah Fisika Kuantum Ditinjau dari Motivasi Berprestasi - Aris Doyan (Department of Physics Education, Universitas Mataram, 2015)
This study aims to determine (1) the influence of quantum and conventional learning model on the learning achievement of quantum physics course, (2) the influence of student achievement motivation on learning achievement of quantum physics course, and (3) the interaction between the quantum and conventional learning model with achievement motivation students' learning achievement of quantum physics course. This type of research is quasi experiment with forms of research design is a 2x2 factorial design. The population in this study were all students of physical education in the school year 2011/2012 VI semester FKIP Mataram University with a sampling technique that random sampling. There are two samples of the study as control and experimental class. The control class given conventional learning while the experimental class was given treatment with quantum learning model. Data were analyzed using analysis of variance (ANOVA) of two different cell. Where, (1) there is the influence of quantum and conventional learning model on the learning achievement of quantum physics course that is obtained significance level (0.047) < (0.05), (2) there is influence student achievement motivation high and low categories of the learning achievement of courses quantum physics is obtained significance level (0.000) < (0.05), and (3) there is no interaction between the quantum and conventional learning model with student achievement motivation on learning achievement of quantum physics course that is obtained significance level (0.190) > (0, 05).